Students' Perceptions in Using the Kahoot! Game on Reading Comprehension Learning - Heni Rochimah; Suyitno Muslim (STAI Hubbulwathan Duri, 2021)
Reading comprehension is an activity to build people's understanding through texts by combining information obtained through texts with their knowledge and experience. Students face problems in reading comprehension, such as difficulty answering questions related to descriptive text, not being able to read the entire text, and confusing new vocabulary. This study aimed to determine how students perceive and improve reading comprehension after using Kahoot! Games as learning media for reading comprehension on description text at State Junior High School in Cilacap. This study uses an experimental sequential mix method with a qualitative descriptive method as the first order followed by a pre-experimental method using a one-group pretest-posttest design. Based on the results of the study, it was found that students' perceptions of using Kahoot! Games tend to be positive, students find learning fun, increase focus and caution, eliminate boredom, and motivate students to read the entire text. Furthermore, there was an increase in students' reading ability as indicated by the paired-sample t-test results where the sig value. the count obtained was 0.002 0.05, and the count obtained was 6.837 table 2.776. Supported by an 18% increase in the average student training results from 66.4 to 81.